2007
DOI: 10.1258/095646207780132460
|View full text |Cite
|
Sign up to set email alerts
|

Yorkshire regional audit of hepatitis B vaccination

Abstract: Practice related to hepatitis B vaccination in Yorkshire genitourinary medicine clinics was audited against targets based on the offer and uptake of vaccination by men who have sex with men (MSM) set by the National Strategy for Sexual Health and HIV (NSSHHIV). Of 254 eligible cases, 226 (93%) were offered vaccination, but only 187 (77%) were offered it at their first visit. Uptake of the first dose of vaccine was 83%, 56% and 82% among eligible MSM, injecting drug users (IDU) and commercial sex workers (CSW),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…However, populations at high risk for STI acquisition and/or transmission, such as MSM, have not been specifically targeted and deserve further special emphasis. Short-course vaccination regimens seem to reach acceptable coverage, 30,31 especially among mobile populations, like commercial sex workers 32 or groups with high rates of migration. Determination of HBV antibody levels after vaccination in HIV-1-infected patients may also be warranted given concerns of effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…However, populations at high risk for STI acquisition and/or transmission, such as MSM, have not been specifically targeted and deserve further special emphasis. Short-course vaccination regimens seem to reach acceptable coverage, 30,31 especially among mobile populations, like commercial sex workers 32 or groups with high rates of migration. Determination of HBV antibody levels after vaccination in HIV-1-infected patients may also be warranted given concerns of effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the risk, drug users rarely complete the 3-dose HBV vaccination program (Rogers & Lubman, 2005). Researchers have shown that accelerated HBV vaccination schedules, such as may be possible in treatment programs, can improve completion rates in this population (Graham & McClean, 2007; Lum et al, 2008; Rogers & Lubman).…”
mentioning
confidence: 99%
“…In this study of those eligible for HBV immunization, only 33.3% completed three doses of HBV vaccination with a further 40% declining it. A regional audit from Yorkshire also reported that injecting drug users had a poor track record in completing HBV vaccination with only 29% receiving the third dose compared to 49% of men who have sex with men [Graham et al, 2007]. Another study amongst street recruited injecting drug users in San Francisco concurred with only a 47% vaccination completion rate [Lum et al, 2003].…”
Section: Discussionmentioning
confidence: 99%